Menjaga Keautentikan Al-Qur’an dalam Keberagaman Indonesia - Yanti, Fitri; Aryani, Vita Latifa; Alfatih, Nur Salsabilah (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2023)
The authenticity of the Qur'an is one of the important aspects in understanding and respecting the Qur'an as a holy book in Islam. The purpose of this study is to find concrete efforts in maintaining the authenticity of the Qur'an in cultural diversity in Indonesia. The term authentic refers to something that is original, valid, or maintains its authenticity and integrity. In the context of the Qur'an, authentic means that the text remains, does not change, and is in accordance with what was conveyed by the Prophet Muhammad. The method used is descriptive analysis. The authenticity of the Qur'an can be seen in three dimensions; first, reading the text; second, writing the text; third, understanding the text. This study found that concrete efforts in maintaining the authenticity of the Qur'an are through collaboration between the community, both scholars, religious leaders, government, and religious adherents in Indonesia.